ICRISAT-Ethiopia Strengthens Fertilizer Advisory Strategy to Boost Agricultural Productivity - Desta, Gizaw (2024)
ICRISAT-Ethiopia, in partnership with the CGIAR Excellence in Agronomy (EiA) initiative, convened a two-day workshop in Durame, Kembata Zone, Central Ethiopia, to advance the scaling of fertilizer advisory services. Held on 23-24 September 2024, the "Scaling Partners’ Network Workshop on Fertilizer Advisory" aimed to enhance collaboration among partners and develop action plans to optimize fertilizer use efficiency in Ethiopia’s diverse agricultural landscapes. This effort is part of the broader Fertilizer Ethiopia Use Case initiative, which seeks to improve smallholder farmers' access to effective, landscape-based fertilizer recommendations.